Can halogen bond energy be reliably estimated from electron density properties at bond critical point? The case of the (A)nZ—YX− (X, Y = F, Cl, Br) interactions. Issue 8 (13th December 2018) - Kuznetsov, Maxim L.
Abstract: Relationships between the YX bond critical point (BCP) properties or the YX distance and the halogen bond interaction energy were analyzed in detail by theoretical methods for the series of structures [(A) n Z—YX] − (X, Y = F, Cl, Br; totally 441 structures). No relationship was found for the whole set of structures or for the series [(A) n Z—FX] −, [(A) n Z—ClX] −, and [(A) n Z—BrX] − . The interaction energies may be roughly estimated from the BCP properties for the series [(A) n Z—YF] −, [(A) n Z—YCl] −, and [(A) n Z—YBr] − as well as for [(A) n Z—YX] − (when (A) n Z is variable, X and Y are constant) with the mean absolute deviation values 2.04‐4.38 kcal/mol. The corresponding recommended relationships are provided and they are significantly different from the popular dependencies deduced previously for other types of noncovalent interactions. Tremendous effect of the computational method and basis set on the relationships under analysis was discovered. Computational results clearly indicate that, for practical purposes, the E int (BCP property) dependencies should be established not simply for each global type of interactions (hydrogen bond, halogen bond, chalcogen bond, etc.) but for each combination of the first and second order atoms taking into account also the computational method and basis set. Abstract : Relationships between the YX interaction energy and electron density based properties at the bond critical point were analyzed in detail for the large statistically significant set of the halogen bond structures [(A) n Z—YX] − (Y, X = F, Cl, Br, 441 structures). The tremendous effect of the computational method and basis set on the relationships under analysis was discovered.